2022
DOI: 10.1530/eje-22-0462
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome and leukocyte telomere length: cross-sectional and longitudinal changes

Abstract: Objective Telomeres are DNA-protein complexes that protect chromosome ends from DNA damage and are surrogate biomarkers of cellular ageing. Current evidence, almost entirely from cross-sectional observations, supports negative associations between leukocyte telomere length (LTL) and adverse lifestyle factors and cardio-metabolic risk factors. Polycystic ovary syndrome (PCOS), the most common gynecological endocrine disorder, is associated with inflammation and oxidative stress, both factors associated with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…On the other hand, Li et al [ 71 ] discovered that PCOS patients had shorter LTL compared to the control group that was 6.16 years older, and LTL was negatively correlated with serum dehydroepiandrosterone sulfate levels. Surprisingly, Pölönen et al [ 72 ] did not observe any leukocyte telomere attrition in PCOS patients aged 31 and 46 years. Similarly, Pedroso et al [ 73 ] reported that in cumulus cells of mature and immature oocytes, TL was not significantly different between PCOS and healthy populations, but TA was significantly increased in PCOS individuals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, Li et al [ 71 ] discovered that PCOS patients had shorter LTL compared to the control group that was 6.16 years older, and LTL was negatively correlated with serum dehydroepiandrosterone sulfate levels. Surprisingly, Pölönen et al [ 72 ] did not observe any leukocyte telomere attrition in PCOS patients aged 31 and 46 years. Similarly, Pedroso et al [ 73 ] reported that in cumulus cells of mature and immature oocytes, TL was not significantly different between PCOS and healthy populations, but TA was significantly increased in PCOS individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Gene variants related to LTL may specifically participate in the pathophysiological processes underlying menorrhagia, which is often linked to abnormal endometrial proliferation, myometrial anomalies and abnormal uterine artery blood flow, among other related factors > [ 89 , 90 ]. These processes may involve systemic factors such as inflammation, oxidative stress and cellular aging, which are reflected in LTL [ 72 , 91 ] PMS is generally thought to be influenced by fluctuations in GABA conductance and neurosteroid levels [ 92 ], which are often more susceptible to external environment and present transient characteristics, inconsistent with the long-term systemic processes predicted by the telomere biology. And beyond that, considering the close interplay between sex hormones and the aforementioned disorders, as well as their impact on TL and TA, further experiments are required in the future to illustrate the biological mechanisms connecting these factors.…”
Section: Discussionmentioning
confidence: 99%